Direct Bilirubin Is More Valuable than Total Bilirubin for Predicting Prognosis in Patients with Liver Cirrhosis - Lee, Han Ah; Jung, Joon Young; Lee, Young-Sun; Jung, Young Kul; Kim, Ji Hoon; An, Hyonggin; Yim, Hyung Joon; Jeen, Yoon Tae; Yeon, Jong Eun; Byun, Kwan Soo; Um, Soon Ho; Seo, Yeon Seok (Gut and liver, 2021)
Most prognostic prediction models for patients with liver cirrhosis include serum total bilirubin (TB) level as a component. This study investigated prognostic performance of serum direct bilirubin (DB) and developed new DB level-based prediction models for cirrhosis.Background/AimsMost prognostic prediction models for patients with liver cirrhosis include serum total bilirubin (TB) level as a component. This study investigated prognostic performance of serum direct bilirubin (DB) and developed new DB level-based prediction models for cirrhosis.A total of 983 hospitalized patients with liver cirrhosis were included. DB-Model for End-Stage Liver Disease (MELD) score was calculated using MELD score formula, with serum DB level replacing TB level.MethodsA total of 983 hospitalized patients with liver cirrhosis were included. DB-Model for End-Stage Liver Disease (MELD) score was calculated using MELD score formula, with serum DB level replacing TB level.Mean age of study population was 56.1 years. Alcoholic liver disease was the most frequent underlying condition (471 patients, 47.9%). Within 6 months, 144 patients (14.6%) died or received liver transplantation due to severe liver dysfunction. The area under the receiver operating characteristic curve (AUROC) for prediction of 6-month mortality with DB level was significantly higher than that with TB level (p<0.001). The AUROC of DB-MELD score for prediction of 6-month mortality was significantly higher than that of MELD score (p<0.001). Patients were randomly divided into training (n=492) and validation (n=491) cohorts. A new prognostic prediction model, "Direct Bilirubin, INR, and Creatinine" (DiBIC) score, was developed based on the most significant predictors of 6-month mortality. In training set, AUROC of DiBIC score for prediction of 6-month mortality was 0.892, which was significantly higher than that of the MELD score (0.875, p=0.017), but not different from that of DB-MELD score (0.886, p=0.272). Similar results were observed in validation set.ResultsMean age of study population was 56.1 years. Alcoholic liver disease was the most frequent underlying condition (471 patients, 47.9%). Within 6 months, 144 patients (14.6%) died or received liver transplantation due to severe liver dysfunction. The area under the receiver operating characteristic curve (AUROC) for prediction of 6-month mortality with DB level was significantly higher than that with TB level (p<0.001). The AUROC of DB-MELD score for prediction of 6-month mortality was significantly higher than that of MELD score (p<0.001). Patients were randomly divided into training (n=492) and validation (n=491) cohorts. A new prognostic prediction model, "Direct Bilirubin, INR, and Creatinine" (DiBIC) score, was developed based on the most significant predictors of 6-month mortality. In training set, AUROC of DiBIC score for prediction of 6-month mortality was 0.892, which was significantly higher than that of the MELD score (0.875, p=0.017), but not different from that of DB-MELD score (0.886, p=0.272). Similar results were observed in validation set.New prognostic models, DB-MELD and DiBIC scores, have good prognostic performance in liver cirrhosis patients, outperforming other currently available models.ConclusionsNew prognostic models, DB-MELD and DiBIC scores, have good prognostic performance in liver cirrhosis patients, outperforming other currently available models.